1997
DOI: 10.1007/s00585-997-0614-0
|View full text |Cite
|
Sign up to set email alerts
|

Field line resonances in discretized magnetospheric models: an artifact study

Abstract: Abstract. For more than two decades numerical models of the Earth's magnetosphere have been used successfully to study magnetospheric dynamic features such as the excitation of ULF pulsations and the mechanism of ®eld line resonance. However, numerical formulations simplify important properties of the real system. For instance the Alfve n continuum becomes discrete because of a ®nite grid size. This discretization can be a possible source of numerical artifacts. Therefore a careful interpretation of any obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Finally, we note that there are roughly six grid cells across the FWHM in these LFM simulations. If the FLRs are not fully resolved in the radial direction, there can be an unphysical leakage of wave energy from the FLR into the fast compressional mode [ Stellmacher et al , 1997]. Thus, the rapid decay of the FLRs in these simulations may not be entirely due to numerical dissipation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we note that there are roughly six grid cells across the FWHM in these LFM simulations. If the FLRs are not fully resolved in the radial direction, there can be an unphysical leakage of wave energy from the FLR into the fast compressional mode [ Stellmacher et al , 1997]. Thus, the rapid decay of the FLRs in these simulations may not be entirely due to numerical dissipation.…”
Section: Discussionmentioning
confidence: 99%
“…Claudepierre et al [2010] were the first to show in the self-consistent, global MHD Lyon-Fedder-Mobarry model (LFM) that fluctuations in the upstream dynamic pressure can produce FLRs in the dayside magnetosphere and to show that they were driven by cavity modes. Even then, others argue that the discretization of Cartesian grids, such as in the SWMF model, and the Alfvén continuum dampen and obscure what is otherwise a localized resonance phenomena, which make them difficult to detect, particularly with broadband sources, or difficult to produce altogether [Stellmacher et al, 1997]. Bellan [1996], for instance, showed that kinetic Alfvén waves mediate the coupling between fast and shear modes, which may suggest FLRs in MHD models are an unphysical, numerical artifact.…”
Section: Introductionmentioning
confidence: 99%